The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1007/s00024-003-2356-6
|View full text |Cite
|
Sign up to set email alerts
|

Time Variation of Parameters Related to the Accelerating Preshock Crustal Deformation in the Aegean Area

Abstract: -The time variation of two parameters related to accelerating seismic deformation before strong earthquakes in the Aegean area is examined. The first is the b parameter of the Gutenberg-Richter relation and the second is the curvature parameter C, which is a measure of deviation of the accelerating preshock deformation from a linear time variation of this deformation. Following two different procedures, it was found that the b value exhibits a decreasing trend prior to the oncoming earthquake, in agreement wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
(28 reference statements)
2
2
0
Order By: Relevance
“…7, along with their estimated errors. A decrease of the b ‐values can easily be seen as the end of the pre‐shock sequence is approached, in agreement with recent relevant studies for main shocks that have already occurred (Karakaisis et al . 2002).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…7, along with their estimated errors. A decrease of the b ‐values can easily be seen as the end of the pre‐shock sequence is approached, in agreement with recent relevant studies for main shocks that have already occurred (Karakaisis et al . 2002).…”
Section: Resultssupporting
confidence: 91%
“…It is observed that the C ‐value continuously decreases as the pre‐shock sequence approaches its end; that is, as the main shock is approached. A similar C ‐value behaviour has been found to precede the strong main shocks that have actually occurred in the Aegean area (Karakaisis et al . 2002).…”
Section: Resultssupporting
confidence: 75%
“…In the majority of the studies carried out within the critical point concept, evidence is presented for growth in the size of the largest earthquakes as the time of the mainshock is approached, which may result in lower b values (Triep and Sykes 1997;Jaumé and Sykes 1999;Mora and Place 1999;Rundle et al 1999;Jaumé 2000;Du and Sykes 2001;Ben-Zion et al 2003;Karakaisis et al 2003;Jaumé and Bebbington 2004;Zöller et al 2006). There exist, however, observations which show that accelerating seismicity is mainly due to a progressive increase in the number (rate) of moderate magnitude events resulting in progressively higher a values (Knopoff et al 1996;Jaumé et al 2000;Rundle et al 2000;Bowman and Sammis 2004;Sammis et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Accelerating preshocks have been observed by many seismologists (Tocher, 1959;Varnes, 1989;Sykes and Jaumé, 1990;Knopoff et al, 1996;Brehm and Braile, 1999;Tzanis et al, 2000;Ben-Zion and Lyakhovsky, 2002;Karakaisis et al, 2003;Scordilis et al, 2004;Papazachos et al, 2005) and interpreted in terms of the critical point dynamics (Sornette and Sammis, 1995;Rundle et al, 2003). Bufe and Varnes (1993) proposed the following relation for the time variation of accelerating preshocks:…”
Section: Introductionmentioning
confidence: 99%